A Simple Clinical Decision Rule To Rule Out Appendicitis In Patients With Nondiagnostic Ultrasound Results. (May 2014) - Leeuwenburgh, Marjolein M. N.; Stockmann, Hein B. A. C.; Bouma, Wim H.; Houdijk, Alexander P. J.; Verhagen, Matthijs F.; Vrouenraets, Bart; Cobben, Lodewijk P. J.; Bossuyt, Patrick M. M.; Stoker, Jaap; Boermeester, Marja A.; the OPTIMAP Study Group; Zehtabchi, Shariar
Abstract Objectives The objective was to identify a set of clinical features that can rule out appendicitis in patients with suspected acute appendicitis and nondiagnostic ultrasound (US) results, allowing safe discharge and next‐day reevaluation without initial computed tomography (CT) or magnetic resonance imaging (MRI). Methods Data on clinical and US evaluation, including a number of prespecified variables potentially associated with acute appendicitis, were prospectively collected in two diagnostic accuracy studies of imaging. These studies included patients with suspected appendicitis seen in the emergency department (ED). For development and validation of the clinical decision rule (CDR), only patients with inconclusive or negative US results were included. There were 199 (of 422) patients in the development cohorts and 120 (of 211) patients in the validation cohort. Logistic regression analysis was used for data from patients with inconclusive or negative US results, and profiles were created of all possible combinations of predictors retained in the multivariable model. A final diagnosis was assigned by an expert panel based on perioperative data, histopathology, and clinical follow‐up of at least 3 months. Results The CDR selected patients after negative or inconclusive US for discharge and next‐day reevaluation without initial CT or MRI if fewer than two of the following predictors were present: male sex, migration of pain to the right lower quadrant, vomiting, and white blood cell (WBC) count higher than 12.0 × 109/L. Applying the CDR in the development set selected 126 of 199 (63%) patients with negative or inconclusive US results for discharge without further imaging. This rule reduced the probability of appendicitis from 26% (51 of 199) in the total group of patients with negative or inconclusive US results to 12% (15 of 126) in the group that would be discharged based on the rule (p = 0.001). In the validation set (n = 120), the decision rule selected 72 (60%) patients for discharge and next‐day reevaluation and reduced the probability of appendicitis from 20% (24 of 120) in the total group to 6% (4 of 72) in the patients selected on the rule (p = 0.001). The negative predictive value of the decision rule in the validation set was 94% (95% confidence interval [CI] = 87% to 98%). In comparison, the negative predictive value of CT in the same group was 99% (95% CI = 93% to 100%, p = 0.14), and that of MRI was 99% (95% CI = 94% to 100%, p = 0.12). Alternative decision rules based on combinations of the present decision rule with C‐reactive protein (CRP) results did not improve selection. Conclusions This newly developed CDR significantly reduces the probability of appendicitis in a large subgroup of patients with negative or inconclusive US results. These patients can be safely discharged for outpatient reevaluation without further initial imaging if proper follow‐up is available. This could assist in lowering the number of ED imaging investigations in patients with suspected appendicitis.